Eco-efficiency and its determinants of major grain-producing areas in China - Chang Qian; Chang Xiang; Yuan Qiuyue; Zhao Yiping; He Xianglin; Tao Xinyuan; Li Yijin (Frontiers in Environmental Science)
Accurately measuring the eco-efficiency of grain production and exploring pathways for its improvements are essential for pormoting green agricultural transformation and achieving China’s “dual carbon” goals. This study assesses the eco-efficiency of grain production in China by incorporating carbon emissions and agricultural non-point source pollution as non-desired outputs, utilizing the SBM-Undesirable model and micro-level survey data from 1,208 farm households in major grain-producing regions. The results suggest that the average eco-efficiency score across these regions is 0.627, marginally above the acceptable threshold and 0.219 points higher than traditional production efficiency, providing empirical support for the Porter hypothesis. Mechanism analysis identifies that eco-efficiency is positively associated with household head’s age, family income, grain-sown area, land quality, and membership in agricultural organizations. In contrast, it is negatively associated with family size, land fragmentation, cropping index, agricultural subsidies, agricultural production outsourcing, and investment in fixed productive assets. Regional heterogeneity analysis confirms the robustness of these findings, showing only minor variations across provinces. Overall, the study offers critical insights into the determinants of eco-efficiency in grain production and proposes actionable strategies to enhance sustainability across China’s agricultural sector.